(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A list of the species belonging to the subgenus Orthocladius s. str. van der Wulp, 187 4 known to occur in the West Palaearctic is here reported. Recent changes in nomenclature are described. Only species well known both as adult males and pupae are considered.